HIV research trials versus standard clinics for antiretroviral-naïve patients: the outcomes differ but do the patients?. (June 2016) - Williams, AJ; Wallis, E; Orkin, C
Exclusion criteria for HIV treatment-naïve drug trials can be stringent and selection bias exists, making it difficult to extrapolate results into the 'real world' clinical situation. We aim to compare the demographics, virological outcomes and psychosocial complexity in adult HIV-infected treatment-naïve patients from our cohort initiating combination antiretroviral therapy (cART) in research trials versus standard clinics. In our unit from 2006 to 2011, 1202 standard clinic and 69 research trial patients initiated cART; every eighth standard clinics patient was included to create a standard clinics:research trials patient ratio of 2:1. Notes were retrospectively reviewed for patient demographics, attendance rates and virological outcomes. Data from 221 antiretroviral-naïve patients starting cART were analysed: 152 standard clinic patients and 69 from research trials. In the research trials group, there was an overrepresentation of men ( p  = 0.041), men who have sex with men ( p  < 0.001), patients of white ethnicity ( p  = 0.01), employed patients ( p  = 0.01) and patients using excessive alcohol ( p  = 0.02). There was equal representation of drug use, depression and referral to psychology, psychiatry and social work in both groups. The research trials group at baseline had significantly higher CD4 counts ( p  < 0.001), lower viral loads ( p  = 0.01) and more patients achieved undetectable viral loads at three ( p  < 0.001), six ( p  < 0.001) and 24 months ( p  = 0.033). There is a prevailing common preconception that participants in clinical trials are uncomplicated, unlike their 'real-life' counterparts. We demonstrated important similarities in psychosocial complexity as well as differences in demographics and virological outcomes in trial and non-trial patients. Clinicians need to be aware of these discrepancies to ensure the facilitation of a heterogeneous population participating in research trials.